2015
DOI: 10.1371/journal.pone.0145061
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Regulates Genes that Are Associated with Response to Endocrine Therapy and Attenuates the Actions of Tamoxifen in Breast Cancer Cells

Abstract: Hereditary, hormonal, and behavioral factors contribute to the development of breast cancer. Alcohol consumption is a modifiable behavior that is linked to increased breast cancer risks and is associated with the development of hormone-dependent breast cancers as well as disease progression and recurrence following endocrine treatment. In this study we examined the molecular mechanisms of action of alcohol by applying molecular, genetic, and genomic approaches in characterizing its effects on estrogen receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 53 publications
2
26
0
Order By: Relevance
“…RNA splicing or transport) has been shown to affect cell cycle and proliferation [ 29 ], although increased RNA processing also may be a consequence of proliferation. Our finding is consistent with experimental studies in which ethanol promoted proliferation in ER+ breast tumor cell lines [ 30 ā€“ 32 ]. In ER+ tumors, we also observed downregulation of lipid metabolism, including the PPAR-gamma signaling pathway.…”
Section: Discussionsupporting
confidence: 93%
“…RNA splicing or transport) has been shown to affect cell cycle and proliferation [ 29 ], although increased RNA processing also may be a consequence of proliferation. Our finding is consistent with experimental studies in which ethanol promoted proliferation in ER+ breast tumor cell lines [ 30 ā€“ 32 ]. In ER+ tumors, we also observed downregulation of lipid metabolism, including the PPAR-gamma signaling pathway.…”
Section: Discussionsupporting
confidence: 93%
“…It was previously reported that alcohol stimulates cell proliferation in ER-positive breast cancer cells [50]. The alcohol-induced phenotypic changes that we report in the TNBC cells include increased cell proliferation, migration, and invasion.…”
Section: Discussionsupporting
confidence: 68%
“…Alcohol and smoking have a potentiating role on E2 and oxidative stress signaling, a fact which warrants large scale studies with natural phytochemicals to assess the impact on BC incidence and associated markers of BC risk . The alcohol induced folate deficiency and consequent decline in cellular methionine synthesis could lead to reprogramming of gene expression, an area in which detailed studies are warranted to assess the impact on BCā€specific gene expression . In addition, global hypomethylation in leukocytes has been shown to be associated with increased risk for BC .…”
Section: Determinants Of Bc Risk: Considerations For Bc Prevention Anmentioning
confidence: 99%
“…55,56 A study on alcohol in ER 1 MCF7 BC cells revealed a positive effect on proliferation and attenuated response to tamoxifen therapy which was mediated by an upregulation of BRAF, a clinical marker of poor response to endocrine therapy in BC. 57,58 Alcohol intake also raises plasma IGF-II, may enhance susceptibility to mammary carcinogenesis and increase invasiveness of BC cells. [58][59][60][61] Obesity represents a chronic proinflammatory condition.…”
Section: Determinants Of Bc Risk: Considerations For Bc Prevention Anmentioning
confidence: 99%
See 1 more Smart Citation